Fibre-based sources from the UV to mid-infrared - Murray,RT; Runcorn,TH; Taylor,JR (2018)
Extensive spectral and temporal versatility are achieved through the integration of nonlinear fibres and crystals with seeded master-oscillator power fibre amplifier configurations through diverse generation processes. Various schemes will be reviewed.